Some characteristics of Southeast English preposition-dropping - Bailey, Laura R. (IBERIA: An International Journal of Theoretical Linguistics, 2019)
Preposition-dropping is widespread in British English varieties, but the construction found in Southeast England differs from the descriptions of Northwest Englishes, patterning more closely with Greek and Romance varieties. The determiner is obligatorily absent, the argument must be a directional Goal, the verb must be semantically weak come or go, and the location must be familiar, anaphoric or a place name. These characteristics are explained if the noun undergoes N-to-D movement to gain a definite interpretation, requiring omission of the determiner and lack of modification, and the null directional preposition to conflates with v for licensing, removing the possibility of manner-of-motion verbs.